Dampak Literasi Keuangan, Literasi digital dan Finansial Teknologi Terhadap Keberlanjutan Bisnis Pelaku UMKM Di Kabupaten Sumbawa - Tomy Dwi Cahyono; Ryan Suarantalla; Jihan Fahira (Jurnal Ilmiah Raflesia Akuntansi, 2025)
The sustainability of MSME business actors is influenced by their ability to adapt to market changes, application of technology, financial literacy, and support from the government and the community in facing various economic challenges. The purpose of this study was to analyze the influence of financial literacy, digital literacy, and financial technology on the sustainability of Small and Medium Enterprises (MSMEs) in Sumbawa Regency. This study uses a quantitative approach with a population consisting of 1,362 MSME actors in Sumbawa Regency. The sampling technique used was total sampling, with the number of samples determined using the Slovin formula, so that 100 respondents were obtained. Data collection was carried out through a questionnaire with a Likert scale from 1 to 4. Data analysis was carried out using multiple linear regression techniques. The results of the study indicate that financial literacy, digital literacy, and financial technology have a positive and significant influence on the sustainability of MSMEs in Sumbawa Regency.